Puerarin as a multi-targeted modulator of lipid metabolism: molecular mechanisms, therapeutic potential and prospects for nutritional translation - Ou, Shu; Liang, Qingzhi; Leng, Yulin; Luo, Ting; Xu, Xin; Xie, Hongyan; Gao, Hong; Li, Jun; Xie, Chunguang (Frontiers in Nutrition, 2025)
Lipid metabolism is a dynamic and intricate process involving the uptake, synthesis, storage and catabolism of lipid compounds in the body. Its homeostasis is crucial for maintaining the health of the organism. The regulatory network of lipid metabolism homeostasis consists of several key molecules, including SREBPs, PPARs, ChREBP, FXR, LXR, AMPK, and ncRNAs. Puerarin (Pue), an isoflavone derivative, has been demonstrated to enhance lipid metabolism by modulating the aforementioned signaling cascades. Pue has found extensive application in the pharmaceutical, food, and nutraceutical industries. Considering the multi-target and multi-pathway pharmacological properties of Pue, the present study focuses on the molecular mechanism of Pue in the regulation of lipid metabolism, the spectrum of metabolic diseases, as well as the limitations of the current study and the prospect of nutritional translation. It is hoped that this study will provide a reference for the regulation of lipid homeostasis and remodeling of lipid metabolism, with the aim of optimizing clinical use and product development.